Literatur Review: Mata Kering Akibat Obat-Obatan - Izzatush Sholihah, Nur (CV RIFAINSTITUT, 2022)
Dry eye disease is a disease that is often encountered and can occur due to several factors. This disease is more common in women than men. The risk factors that can cause dry eyes are divided based on individual characteristics, environment, chronic disease, autoimmune disease, medications and history of injury. The writing of this article was obtained from various sources in the form of scientific journals and guidelines for related institutions. Source searches were carried out on various online portals such as Medscape, NCBI, Google Scholar and other health websites with the keyword “Dry Eye Disease”, “Dry Eye Syndrome”, “Medications Causes Dry Eyes” Dry eye disease is a disease that is often encountered and occurs because it is multifactorial and can affect the quality of life and interfere with vision, especially when carrying out daily activities. One of the factors that cause dry eyes, namely the use of drugs, both topical drugs and systemic drugs. Concurrent use of five or more medications can increase the occurrence of dry eye. Management of dry eyes can be given artificial tears and stop using medications that trigger dry eyes or replace the drug with another drug. Dry eye disease can be caused by the use of drugs, both topical and systemic drugs. Treatment that can be done, namely by giving artificial tears and avoiding systemic or topical ophthalmic drugs that cause dry eyes.